Looking Through a Different Lens: Patient Satisfaction With Telemedicine in Delivering Pediatric Fracture Care. (September 2019) - Sinha, Neha; Cornell, Max; Wheatley, Benjamin; Munley, Nicole; Seeley, Mark
Abstract : Introduction: Telemedicine may transform health care by overcoming geographical and travel-associated barriers to patient care. This study assesses patient satisfaction with telemedicine for fracture care. Methods: Two groups of patients were compared from suburban/rural Pennsylvania. One group reported to a regional medical center for real-time video consultation with a pediatric orthopaedic surgeon facilitated by a physician's assistant. The other group underwent conventional outpatient clinic visits at a tertiary care hospital. The distance between the tertiary care hospital and the regional medical center was 69 miles. New or follow-up fracture patients not living in the vicinity of either medical center were included. A satisfaction survey and questionnaire were administered to both groups at the end of their visit. Results: One hundred sixty-seven patients returned the questionnaires (66 conventional and 101 telemedicine). Telemedicine visits decreased indirect and direct costs ( P = 0.032). Travel costs and travel times were lower ( P < 0.001) in the telemedicine group. Patient satisfaction was similar. Only 8 of 101 patients in the telemedicine cohort preferred their next visit to be a conventional follow-up. Discussion: Utilization of video consultation and trained physician assistants to provide pediatric orthopaedic care across suburban/rural areas can increase pediatric orthopaedic surgeon access and decrease travel costs while maintaining patient satisfaction.